Islamic feminist discourse: origins and development in the Muslim World - Muhamad Shukri, Abdul Salam (2011)
This paper traces the origins of the feminist discourse in the West and the different strands of this discourse so as to understand better the feminist debates and the root of Islamic feminist discourse within the feminist movements generally. It concludes that the concept of feminism, being a modern concept which has developed through different phases in the Western part of the world, like all isms in the modern world, the values it came to be associated with – especially in its radical form – is an antithesis of what Islam stands for and is thus not acceptable to many Muslims. However, Muslim scholars and many Muslim women have presented this ideology in an Islamic form and tried to use the same idea to fight for the emancipation of women while qualifying their feminism with Islam.